2022
DOI: 10.3390/ani12192685
|View full text |Cite
|
Sign up to set email alerts
|

Noseband Fit: Measurements and Perceptions of Canadian Equestrians

Abstract: Recent concerns regarding horse welfare during competition has highlighted the occurrence of overtightened nosebands on competition horses. Current rules are often vague—e.g., “nosebands may never be so tightly fixed as to harm the horse.” To investigate the need and acceptance prior to any rule changes Equestrian Canada (EC) launched a pilot noseband measuring project. Nineteen officiating stewards measured noseband fit using the ISES taper gauge (TG) at 32 equestrian events of various disciplines in 2021. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The use of these tight nosebands is controversial, and various studies aimed to investigate their various effects on the horse more carefully. Chewing movements indicating suppleness that are desired in equitation are almost impossible with tight nosebands (Clayton & Williams, 2022 , Doherty et al., 2016 , 2017 , Merkies et al., 2022 , Visser et al., 2019 ). In addition, direct physical damage can also occur because of the exposure to a noseband that is too tight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of these tight nosebands is controversial, and various studies aimed to investigate their various effects on the horse more carefully. Chewing movements indicating suppleness that are desired in equitation are almost impossible with tight nosebands (Clayton & Williams, 2022 , Doherty et al., 2016 , 2017 , Merkies et al., 2022 , Visser et al., 2019 ). In addition, direct physical damage can also occur because of the exposure to a noseband that is too tight.…”
Section: Discussionmentioning
confidence: 99%
“…Tight and restrictive nosebands are still common in equestrian sports despite the equestrian associations' strive for regulations during competitions (FEI Inside, 2023). It has been shown that there is a widespread tendency to tighten the noseband to a substantially higher level of tightness than that suggested in equestrian guidelines (Clayton & Williams, 2022, Doherty, Conway, et al, 2017, Merkies et al, 2022, Uldahl & Clayton, 2019, Visser et al, 2019, Weller et al, 2020. The use of these tight nosebands is controversial, and various studies aimed to investigate their various effects on the horse more carefully.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines of the German Equestrian Federation (Fédération Equestre Nationale; FN) recommend that two fingers of an adult should be placed between the noseband and the bridge of the nose of the horse. However, this is not always met in practice [ 4 , 5 ]. Various studies have evaluated the impact of tight nosebands on so-called stress parameters, such as cortisol, heart rate variability and eye temperature measured by infrared thermography, as well as horses’ behavior [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%